Konflik Tentara Nasional Indonesia Dengan Organisasi Papua Merdeka - Joshua Victor Hendriko Simaela; Josina Augustina Yvonne Wattimena; Johanis Steny Franco Peilouw (Faculty of Law Universitas Pattimura, 2023)
The OPM conflict that occurred has been going on for quite a long time, since the differences of opinion between Indonesia and the Netherlands at the 1949 Round Table conference in international law have regulated the settlement of the dispute. Until now there are still shootouts between the Military Forces and OPM members. The purpose of this research is to find out if the TNI-OPM conflict can be qualified as a non-international conflict. To find out the resolution of the conflict according to international humanitarian law the research method used is normative juridical research. The problem approach used is a conceptual approach, statutory approach, historical approach, and case approach. The legal materials used are primary legal materials, secondary legal materials and tertiary legal materials. Collection of legal materials using literature and then analyzed using qualitative analysis methods. Based on the results of research and discussion that the conflict between the OPM and the TNI is a non-international armed conflict because the conflict occurs within the State of Indonesia itself, even though this conflict is non-international in nature, the resolution itself has been regulated in international law based on the 1899 and 1907 Hague Conventions, The 1949 Geneva Convention and the 1977 Additional Protocol to its settlement can be carried out peacefully by way of negotiation, mediation, good offices and fact finding, arbitration and judicial settlement.